Elevation and spatial structure explain most surface-water isotopic variation across five Pacific Coast basins - McGill, L.M. (J Hydrol (Amst), 2020)
The stable isotope ratios of stream water can be used to trace water sources within river basins; however, drivers of variation in water isotopic spatial patterns across basins must be understood before ecologically relevant and isotopically distinct water sources can be identified and this tool efficiently applied. We measured the isotope ratios of surface-water samples collected during summer low-flow across five basins in Washington and southeast Alaska (Snoqualmie, Green, Skagit, and Wenatchee Rivers, and Cowee Creek) and compared models (isoscapes) describing the spatial variation in surface-water isotope ratios across a range of hydraulic and climatic conditions. We found strong correlations between mean watershed (MWE) elevation and surface-water isotopic ratios on the windward west side of the Cascades and in Alaska, explaining 48–90% of variation in δ(18)O values. Conversely, in the Wenatchee basin, located leeward of the Cascade Range, MWE alone had no predicative power. The elevation relationship and predictive isoscapes varied between basins, even those adjacent to each other. Applying spatial stream network models (SSNMs) to the Snoqualmie and Wenatchee Rivers, we found incorporating Euclidean and flow-connected spatial autocovariance improved explanatory power. SSNMs improved the accuracy of river water isoscapes in all cases; however, their utility was greater for the Wenatchee basin, where covariates explained only a small proportion of total variation. Our study provides insights into why basinscale surface-water isoscapes may vary even in adjacent basins and the importance of incorporating spatial autocorrelation in isoscapes. For determining source water contributions to downstream waters, our results indicate that surface water isoscapes should be developed for each basin of interest.